E-Library SMAK Frateran Maumere Berbasis Mobile - Diaz, Ludgardis Amadea; Utami, Wahyu Sri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
In this digital era, the need for fast and easy access to information is increasing, including in the world of libraries. The Android-based e-library is here as a solution to provide wider and more practical access for users to access various reading materials. The system is designed to provide a user-friendly platform, allowing users to search, borrow, and read a variety of e-books directly from their Android devices. With features such as advanced search, book recommendations, and integrated loan and return management, this e-library aims to improve the reading experience and efficiency in library management. It is hoped that the implementation of an Android-based e-library will not only facilitate access to information but also encourage interest in reading among the wider community, as well as support digital transformation in the library sector.